Australian Broadband Regulation Reviewed - Barry, Troy Sidney (Journal of Telecommunications and the Digital Economy, 2018)
This article establishes the relationship between the condition of Australian broadband services and Australia’s history of broadband regulation. It briefly surveys the history of the industry in terms of government action and firms’ responses. It reviews research on the effects of regulation and industry concentration internationally, which indicates that the effects of widely deployed policies are often small or undetectable. The article uses these findings to build models of national broadband prices, penetration and quality. The models are verified using recent statistics from developed economies, confirming that outcomes are little affected by access regulation, and also not by market concentration. Penetration and quality are strongly affected by technology factors. The models and the regulatory history are used to explain the condition of Australian broadband services, and to extract lessons applicable to future policy development.